Keragaman Tumbuhan Invasif di Perkebunan Sawit PT Perkebunan Nusantara II Deli Serdang, Sumatra Utara: Diversity of Invasive Plant Species in Palm Oil Plantation PT Perkebunan Nusantara II Deli Serdang, North Sumatra - Rambe, Saidah Putri; Sulistijorini; Chikmawati, Tatik (Departemen Biologi, Institut Pertanian Bogor, 2024)
Several species of weeds, categorized as invasive plants, are among the factors inhibiting plantation productivity. The uncontrolled spread and growth of these invasive plants can lead to both economic and ecological losses. This study aimed to analyze the diversity of invasive species in the palm oil plantation area of PT Perkebunan Nusantara II. Plant samples were collected by establishing sample plots in three different blocks using purposive sampling. Additionally, species identification and data analysis were conducted, including the Important Value Index (IVI), diversity index, similarity index, and evenness index. A total of 20 invasive species out of 61 weed species, belonging to 14 families, were identified. The invasive species are primarily herbs, climbing plants, and shrubs. Invasive species are dominated by families Poaceae and Asteraceae. Asystasia gangetica, Mitracarpus hirtus, Peperomia pellucida, and Phyllanthus urinaria were found in all three blocks. However, based on the IVI value, only three invasive species were found to significantly affect the community: P. urinaria, Setaria plicata, and P. pellucida.